Were Jews in interwar Poland more educated?. (September 2020) - Abramitzky, Ran; Halaburda, Hanna
Abstract: In the context of interwar Poland, we find that Jews tended to be more literate than non-Jews, but show that this finding is driven by a composition effect. In particular, most Jews lived in cities and most non-Jews lived in rural areas, and people in cities were more educated than people in villages regardless of their religion. The case of interwar Poland illustrates that the Jewish relative education advantage depends on the historical and institutional contexts.